PENGEMBANGAN LKPD CERITA RAKYAT SABU “KOLO MERABU” UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI HIDUP RUKUN DI KELAS III SD INPRES MAPOLI KOTA KUPANG - Febryella Tantika Riwu Teta; Marselina Nitte, Yulsy; Lioba Nahak, Roswita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Tantika, Ella, 2026. Development of LKPD Based on Sabu Folklore “Kolo Merabu” on the Topic of Living in Harmony in Pancasila Education for Grade III Students at SDI Mapoli Kupang City. Yulsy Marselina Nitte, S.H., M.Pd and Roswita Lioba Nahak, S.Pd., M.Pd as supervisors I and II. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University Kupang. Folklore-based LKPD has an important role in learning activities. The existence of LKPD based on the Sabu folklore “Kolo Merabu” is expected to be used by teachers and students of Grade III SDI Mapoli Kupang City to improve students’ understanding and learning outcomes in Pancasila Education on the topic of living in harmony. The purpose of this study was to determine the feasibility, attractiveness, and effectiveness of LKPD based on the Sabu folklore “Kolo Merabu” in improving student learning outcomes. The type of research used in this study was Research and Development (R&D) using the ADDIE development model consisting of Analyze, Design, Development, Implementation, and Evaluation. The ADDIE development model consists of five stages. The first stage was Analyze, which involved analyzing teacher needs, curriculum needs, and student characteristics. The second stage was Design, which involved designing the LKPD based on the Sabu folklore “Kolo Merabu”. The third stage was Development, which involved developing the LKPD through validation by material experts, language experts, and media experts. The fourth stage was Implementation, where the developed LKPD was tested on a group of 22 Grade III students of SDI Mapoli Kupang City. The fifth stage was Evaluation, in which the researcher used tests and questionnaires to determine student learning outcomes and evaluate the quality of the product. The research instruments used in this study were validation sheets, learning outcome tests, and questionnaires administered to teachers and students. The data analysis techniques used included validity testing, reliability testing, normality testing, linearity testing, paired sample t-test, and N-Gain analysis. The results of the study showed that the LKPD based on the Sabu folklore “Kolo Merabu” was feasible for use in learning activities. The validation results indicated that the LKPD obtained a very feasible category from material experts, language experts, and media experts. The validity test results showed that all 15 test items were valid, while the reliability test obtained a Cronbach’s Alpha value of 0.765, indicating that the instrument was reliable. Teacher responses to the LKPD obtained a score of 55 out of a maximum score of 56 with a percentage of 98.21% in the Very Good category. Student responses obtained an average percentage of 95.65% in the Very Good category. The paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant effect of the use of LKPD on student learning outcomes. The N-Gain value of 0.7639 was included in the high category. Thus, the LKPD based on the Sabu folklore “Kolo Merabu” was declared feasible, attractive, and effective for use in Pancasila Education learning on the topic of living in harmony.